The Effect of Green Accounting on Company Performance with Good Coorporate Governance as a Moderating Variable - Anggraeni, Rasmi Nur; Mande, Henni; Suryanto, Nur Rizkianti; Raheni, Cahyaning (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Researchers have a number of beliefs and experiments that must be proven, namely that the Green Accounting variable can have a positive relationship and a significant influence on company performance, which consists of environmental performance and company performance, because the better the expenditure to maintain and preserve the environment, the company will be far from conflicts caused by pollution. environment, fines due to environmental pollution, and even natural disasters. However, these expenses will not be very significant if there is no good corporate governance. Based on this, this research aims to analyze the influence of the Green Accounting variable on Company Performance with Good Corporate Governance as a moderating variable. This research is quantitative research with an explanatory approach. The data used in this research was collected using a questionnaire method from 150 employees in the B3 waste supervisory and management department and 150 employees in the finance department. This data can also be called primary data. The data collected from the questionnaire method was analyzed using the smart PLS 4.0 analysis tool.